Demographic Analysis of Emergency Department Patients at the Ruijin Hospital, Shanghai - Wim Lammers; Willem Folmer; Esther M. M. Van Lieshout; Terry Mulligan; Jan C. Christiaanse; Dennis Den Hartog; Jianjing Tong; Yiming Lu; Peter Patka (Emergency Medicine International)
Emergency medicine is an upcoming discipline that is still under development in many countries. Therefore, it is important to gain insight into the organization and patients presenting to the Emergency Department (ED). The aim of this cross-sectional study was to provide an epidemiological description of complaints and referrals of the patients visiting the ED of the Ruijin Hospital in Shanghai, China. A questionnaire was developed and completed for a convenience sample of all patients presenting to the Triage Desk of the ED. The study was performed in June 2008. A total of 2183 questionnaires were completed. The most common complaints were fever (15%), stomach/abdominal pain (15%), vertigo/dizziness (11%), and cough (10%). Following triage, patients were predominantly referred to an internist (41%), neurologist (14%), pulmonologist (11%), or general surgeon (9%). This study provides a better understanding of the reason for the ED visit and the triage system at the ED of the Ruijin Hospital. The results can be used in order to improve facilities appropriate for the specific population in the ED.